(untitled) (Scientia Agropecuaria, 2020)
The Criollo cocoa bean is classified as “fine” or flavor cocoas, being perceived as aromatic or smooth with fruity, raisin, floral, spicy, nutty, molasses, and caramel notes. In the present work, gas chromatography coupled to mass spectrometry was used to study the volatile fingerprint of roasted and unroasted Criollo cocoa from four Amazon districts: Nieva, Cajaruro, Copallín and La Peca located in the Amazon Region of Peru. The results showed that the main sensory perception of cocoa is fruit, and this decreases as the roasting intensity increases. A total of 96 volatile compounds were found, of which the esters had a greater presence in the volatile fingerprint of Criollo cocoa. Propyl acetate (3.5%), acetoin acetate (1.3%) and diethyl succinate (0.8%) were found as the characteristic compounds of Criollo cocoa analyzed, which give it its fruit perception. The linalool/benzaldehyde ratio was between 0.56 and 0.89 for La Peca and Cajaruro cocoa. Principal component analysis revealed that the Criollo cocoa in each district has a different volatile fingerprint, whether it is roasted or unroasted beans. The roasting process generates a greater differentiation of the volatile fingerprint of Criollo cocoa.